Here comes trouble stories from my life - Moore, Michael 1954 April 23- (Grand Central Publishing, 2011)
Capturing the zeitgeist of the past fifty years, yet deeply personal and unflinchingly honest, "Here Comes Trouble" takes readers on an unforgettable, take-no-prisoners ride through the life and times of Michael Moore. No one will come away from this book without a sense of surprise about the Michael Moore most of us didn't know.